Does air pollution matter in a supplier's trade credit strategy? Evidence from an emerging market - Jianhua Tan; Xuehui Zhang; Peng Zhang; Kam C. Chan (Borsa İstanbul Review, 2021)
This study analyzes the impact of air pollution on the city in which customers are located on the trade credit strategy of their suppliers. Following the framework of environmental stress theory, we hypothesize that suppliers change their trade credit strategy to grant less trade credit to their customers located in cities with severe air pollution. Our findings are consistent with our hypothesis. We find that the adverse effects of air pollution occur through financial constraints, operating risk, and customers' default risk, corroborating the underlying logic of our proposed hypothesis. Additional analyses suggest that changes in a supplier's trade credit are more pronounced when a customer is in a polluting industry, has low total factor productivity, receives fewer government subsidies, has fewer bank loans, is far from its suppliers, and has poor inventory management.
Keywords: 330; Air pollution; Environmental stress theory; Trade credit strategy